Thermal studies on aerogel-filled sandwich composite structures - Chen, Kenny Weixiong. (2012)
Thermal insulation properties of commercially developed aerogel granules (Cabot® Nanogel) & their incorporation into sandwich composite (GFRP) structures in order to achieve optimal thermal insulation are studied & discussed in this report.